2007
DOI: 10.1093/jac/dkm457
|View full text |Cite
|
Sign up to set email alerts
|

Potential synergy activity of the novel ceragenin, CSA-13, against clinical isolates of Pseudomonas aeruginosa, including multidrug-resistant P. aeruginosa

Abstract: CSA-13 showed concentration-dependent activity against clinical isolates of P. aeruginosa, including multidrug-resistant P. aeruginosa. The addition of cefepime or ciprofloxacin to CSA-13 enhanced bacterial kill, achieving early synergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 21 publications
4
77
1
4
Order By: Relevance
“…For example, ceragenins retain activity against methicillin-resistant Staphylococcus aureus, [21] colistin-resistant Klebsiella pneumoniae [22,23] and fluconazoleresistant Candida albicans [24] Efforts to generate resistance to selected ceragenins have resulted in relatively small changes in susceptibility, due to modifications of the lipid A portion of LPS, but high levels of resistance have not been observed [22,25]. Multiple in vivo studies have demonstrated that ceragenins are well tolerated in specific tissues and retain their antibacterial activities [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ceragenins retain activity against methicillin-resistant Staphylococcus aureus, [21] colistin-resistant Klebsiella pneumoniae [22,23] and fluconazoleresistant Candida albicans [24] Efforts to generate resistance to selected ceragenins have resulted in relatively small changes in susceptibility, due to modifications of the lipid A portion of LPS, but high levels of resistance have not been observed [22,25]. Multiple in vivo studies have demonstrated that ceragenins are well tolerated in specific tissues and retain their antibacterial activities [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Potency of the ceragenins varies from compound to compound, based on side groups added, solubility, and degree of charge (with greater positive charge correlating with greater antimicrobial activity). Importantly, ceragenins can kill bacterial pathogens that are resistant to multiple antibiotics, including methicillin-resistant Staphylococcus aureus (9) and multidrug-resistant Pseudomonas aeruginosa (8). They are also acid stable and water soluble.…”
mentioning
confidence: 99%
“…40 Ceragenins possess strong bactericidal activity against Gram-positive and Gram-negative bacteria, including MDR strains. [41][42][43][44][45][46] Significant membrane activity of CSAs results in bacterial membrane permeabilization and depolarization. 44,47 Previous studies indicate that antimicrobial activity of ceragenins against Gram-negative bacteria is usually lower than the effects against Gram-positive species.…”
Section: Discussionmentioning
confidence: 99%